Extraction and biological activity of allicin from In Vitro cultured garlic (Allium sativum L.) - Sabeh D. AlUtbi (University of Thi-Qar Journal of Science, 2019)
The shoots of garlic (Allium sativum L.) were initiated on MS (Murashige and Skoog) medium supplemented with Benzyl adenine (BA), 4mg/L which is significantly the best among other treatments (1,2,3,5mg/L); the shoots also initiated from shoot tip in the presence of combination (NAA, 3mg/L and kinetin, 1mg/L); callus was also initiated from basal disc and shoot tip in the presence of combination (NAA, 5mg/L and kinetin 0.5mg/L) and (2,4-D, 1.5mg/L and kinetin 0.5mg/L).Rfs values of extracted allicin from bulbs, shoots, and callus were 0.97, 0.94, 0.95 respectively and the amount percentages were 1.3%, 1.8%, 2.2% respectively; identification of allicin by IR spectrum showed the similarity between the groups of extracted allicin from shoots and those of extracted allicin from bulbs (Standard); identification of allicin by UV showed one band at wave length 338nm for extracted allicin from shoot and 296nm for extracted allicin from bulbs (Standard).The results also showed the difference in the biological activity of extracted allicin from callus, shoots and bulbs of garlic toward Staphyllococcus aureus and Escherichia coli.